Manajemen Kepala Sekolah Dalam Optimalisasi Pemanfaatan Platform Merdeka Mengajar - Rahayu, Yayu Sri; Pristy, Marlin; Yuliawati, Yuyun; Anwar, Ridwan; Rostini, Deti; Wasliman, Eva Dianawati (Universitas Pendidikan Mandalika, 2024)
Abstract: One of the efforts of the Ministry of Education and Culture to support the implementation of the Merdeka curriculum is to carry out a learning transformation process, with one focus being digital transformation. So the Merdeka Mengajar Platform, known as PMM, is an application that is expected to be able to support the development of the competencies of educators and education staff in Indonesia. This research discusses the Principal's efforts to optimize the use of the Merdeka Mengajar Platform (PMM) at Al-Ma'moen High School as a response to the learning crisis after the Covid-19 pandemic. In this case, school principals must implement appropriate management so that the use of digital transformation, especially in the Merdeka Mengajar Platform, can be optimal. The aim of this research is to obtain an overview of the principal's management in increasing the optimization of the use of PMM at Al-Ma'moen High School. This research uses a qualitative approach with a case study method. The results of data analysis show that the school principal's managerial leadership in increasing the optimization of the use of the Merdeka Mengajar Platform has been quite effective. The school principal has carried out these management functions, so that the planned program can run well and achieve the predetermined goals.Keywords: Principal Management, Digital Transformation. Abstrak: Salah satu upaya dari Kemendikbudristek untuk mendukung implementasi kurikulum Merdeka tersebut adalah melakukan proses transformasi pembelajaran, dengan fokus salah satunya adalah transformasi digital. Maka Platform Merdeka Mengajar yang dikenal dengan PMM ini menjadi aplikasi yang diharapkan mampu mendukung pengembangan kompetensi pendidik dan tenaga kependidikan di Indonesia. Penelitian ini membahas upaya Kepala Sekolah dalam mengoptimalkan pemanfaatan Platform Merdeka Mengajar (PMM) di SMA Al-Ma'moen sebagai respons terhadap krisis pembelajaran pasca-pandemi Covid-19. Dalam hal ini, kepala sekolah harus menerapkan manajemen yang tepat agar pemanfaatan transformasi digital terutama dalam Platform Merdeka Mengajar ini dapat optimal. Tujuan penelitian ini adalah untuk memperoleh gambaran tentang manajemen kepala sekolah dalam meningkatkan optimalisasi pemanfaatan PMM di SMA Al-Ma’moen. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Hasil analisis data menunjukan bahwa kepemimpinan manajerial kepala sekolah dalam meningkatkan optimalisasi pemanfaatan Platform Merdeka Mengajar telah berjalan cukup efektif. Kepala sekolah sudah melaksanakan fungsi manajemen tersebut, sehingga program yang sudah direncanakan dapat berjalan dengan baik dan dapat mencapai tujuan yang telah ditentukan.Kata Kunci: manajemen kepala sekolah, transformasi digital.